2003
DOI: 10.1093/humrep/deg202
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in human sperm influences time to pregnancy

Abstract: The data suggest that oxidative damage to sperm DNA influences fecundity and the level of damage is relatively constant within an individual and not influenced by smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 38 publications
4
105
0
8
Order By: Relevance
“…Studies have shown that sperm DNA damage is associated with a prolonged time to pregnancy and a very low probability of achieving a natural pregnancy [Evenson et al 1999;Giwercman et al 2010;Loft et al 2003;Spano et al 2000]. A systematic review and meta-analysis of published natural pregnancy studies clearly correlates sperm DNA damage and failure to achieve a natural pregnancy (odds ratio (OR) = 7.01, 95% CI 3.68, 13.36, p < 0.001; Table 1).…”
Section: Relationship Between Sperm Dna Damage and Pregnancymentioning
confidence: 97%
“…Studies have shown that sperm DNA damage is associated with a prolonged time to pregnancy and a very low probability of achieving a natural pregnancy [Evenson et al 1999;Giwercman et al 2010;Loft et al 2003;Spano et al 2000]. A systematic review and meta-analysis of published natural pregnancy studies clearly correlates sperm DNA damage and failure to achieve a natural pregnancy (odds ratio (OR) = 7.01, 95% CI 3.68, 13.36, p < 0.001; Table 1).…”
Section: Relationship Between Sperm Dna Damage and Pregnancymentioning
confidence: 97%
“…Although sperm are highly differentiated cells with a characteristic morphology that render their DNA compact and protected from surrounding toxic substances [4], sperm DNA can be damaged through three major mechanisms: (i) oxidative stress -the main cause of sperm DNA fragmentation in mature sperm [5], (ii) alterations in chromatin packing [6], and (iii) abortive apoptosis [7]. About 10 % of fertile men and 20-25 % of infertile men present high levels of sperm DNA damage [8], which is associated with reduced reproductive potential [9][10][11][12] and embryo quality [13] and elevated miscarriage rates [14]. Moreover, it increases the risk of iatrogenic transmission of genetic defects during assisted reproduction techniques (ART) [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, using donor oocytes (18-35 years old), no significant differences between DNA fragmentation and reproductive outcomes were found [34]. In contrast, an inverse relationship between sperm DNA oxidation (levels of 8-oxoDG) and monthly fecundity rate has been found in a naturally conceiving population where the average woman age was 25 [35], similarly to a donor conception cycle, while Esbert and colleagues [36] found that DNA damage in sperm was unrelated to fertilization, embryo morphology, and pregnancy rates in IVF or ICSI with own or donor oocytes.…”
Section: Relationship Between Ros and Reproductive Outcomesmentioning
confidence: 92%